IMPLEMENTATION AND ISSUES OF EDUCATION POLICY AMIDST THE PANDEMIC ON STUDENT LEARNING PROCESSES - Wahyudi Widodo (Jurnal Scientia, 2023)
The purpose of policy implementation is to set a direction so that policy objectives can be realized. This study aims to describe the policy implementation process, including education policy. Then during the Covid-19 pandemic, it changed the entire structure of human life, especially in the world of education. This requires education to change and adapt quickly to continue the learning process. This journal was written by reviewing related articles about online learning policies which are considered as a solution to continue the learning process when schools are closed to avoid the spread of the virus. However, on the other hand, this policy has had an impact on the process of knowledge transformation, both for students, teachers and parents or families.